Polskie ustawodawstwo antyterrorystyczne. Wybrane zagadnienia - Antonów, Radosław (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Terrorism is, undoubtedly, a threat to Poland’s security, which is why the state needs to undertake actions with regard to many aspects of its anti-terrorist policy, beginning with legislation and ending with information and education. An important step in the strengthening of Poland’s anti-terrorist security was the adoption of the Anti-Terrorism Act of 10 June 2016. When applied in a responsible manner by the relevant agencies, the Act can be an effective tool in the fight against terrorism. Importantly, it can be used to launch pre-emptive actions effectively preventing terrorist activities within the territory of the Republic of Poland. However, it should be noted that this piece of legislation is to be used only to protect the citizens against terrorist attacks. It cannot, therefore, be used for purposes other than anti-terrorist actions.
Keywords: terroryzm; bezpieczeństwo; wojna z terroryzmem; wojna asymetryczna